The Tenth Tallinn Print Triennial. - Hain, Jüri; Tallinn Art Hall, Tallinn; City Gallery, Tallinn; Vaal Galerii, Tallinn; Gallery of the Russian Embassy in Estonia, Tallinn; Draakon Galleri, Tallinn; The Tenth Tallinn Print Triennial, Tallinn, 1995 (Tallinn : Association of Estonian Printmakers, 1995)
Heam*agi, Inga ; Jõkalda, Loit ; Jöekalda, Virge ; Kalm, Anu ; Kann, Voldemar ; Kask, Eve ; Keerend, Avo ; Kuusing, Kai ; Lapin, Leonhard ; Lestberg, Ly ; Liiva, Silvi ; Meel, Raul ; Mäetamm, Marko ; Neidre, Naima ; Ootsing, enno ; Põllu, Kaljo ; Saks, Reti ; Siib, Liina ; Summatavet, Triin ; Tihemets, Evi ; Tolli, Vive ; Vahtrapuu, Aili ; Vasserman, Benjamin ; Viik, Urmas ; Vinn, Vello ; Vint, Aili ; Vint, Mare ; Üksine, Marje ; Ancane, Banuta ; Berkmane, Ineta ; Bormanis, Egils ; Dragune, Maija ; Dzervite, Vineta ; Grjazeva, Jekaterina ; Grase, Marita ; Grisins, Vladislava ; Heinrihsone, Helena ; Jansone-Zirnite, Anita ; Kalnacs, Andrejs ; Krepics, Imants ; Libiete, Ilze ; Markevica-Caruka, Ieva ; Muiflude, Malda ; Murovskis, Janis ; Nikitins, Arturs ; Ozola, Arta ; Sietins, Guntars ; Subacs, Maris ; Savelis, Olafs ; Zirnite, Nele ; Daniliauskaite, Viktorija ; Dauksaite-Guobiene, Irena ; Grafliene, Danute ; Grigaliunas, Kestutis ; Jurkunas, Vytautas ; Kriauciunaite, Elvyra-Katalina ; Radaviciute, Diana ; Ramunaite, Aiste ; Saladflius, Edmundas ; Salciute, Laisve ; Saltenyte, Nijole ; Slektavicius, Gerardas ; Stancikaite, Birute ; Stauskaite, Jurate ; Vaigeltaite, Roberta ; Vasiliunas, Kestutis ; Veliuviene, Ramune ; Vertelkaite, Egle ; Vilutis, Mikalojus-Povilas ; Zvilius, Alfonsas ; Dover, Peter ; Edalatpour, Seyed M.S. ; Grater, Julian ; Grimes, Oona ; Hansbra, Brendan Patrick ; Hewitt, John ; Klimowski, Andrzei ; Lewandowski, Simon ; Mumberson, Stephen ; Nevin, Pete ; Pacheco, Ana Maria ; Rahmanzadeh, Akram ; Wootton, Mick ; Basaglia, Vittorio ; Freiles, Antonio ; Licata, Riccardi ; Sene, Nicola ; Soffiantino, Giacomo ; Vaccarone, Francesco ; Vecchiet, Franco ; Vizzini, Andrea ; Zigaina, Giuseppe ; Zotti, Carmelo ; Hamano, Nobuko ; Imoto, Hideki ; etc.
geboortedatum per kunstenaar
Engels & Ests
The Tenth Tallinn Print Triennial, Tallinn, September 22 - October 15, 1995, Tallinn Art Hall, Tallinn ; Gallery of the Tallinn Art Hall, Tallinn ; City Gallery, Tallinn ; Vaal Gallerii, Tallinn ; Gallery of the Russian Embassy in Estonia, Tallinn ; Draakon Galleri, Tallinn
kunstcatalogus